379 Injuries among youth mountain bike racers: first year data from a nation-wide injury surveillance system in the united states. (3rd March 2020) - Ehn, Meredith; Cushman, Daniel M; Teramoto, Masaru; Spencer, Chris; Willick, Stuart
Abstract : Background: Youth mountain bike racing is a rapidly growing sport in the United States. An injury surveillance system (ISS) was implemented through a collaboration between University of Utah researchers and the National Interscholastic Cycling Association (NICA) to better understand injury characteristics in this sport and pursue data-driven injury prevention strategies. Objective: Describe types of and factors associated with injuries sustained by youth mountain bike racers during NICA-sanctioned mountain bike racing and training. Design: A longitudinal ISS was developed using a web-based system. Data were collected from NICA leagues during the 2018 season. Designated injury reporters from each team received weekly emails with an exposure form and an incident report form. Setting: Nation-wide youth mountain biking leagues in the United States. Participants: 18, 577 student-athletes in grades 8–12 participated in the 2018 season, the inaugural year of the NICA ISS. Assessment of risk factors: Variables analyzed included injury characteristics, athlete demographics, trail conditions, incline at crash site, weather, crash circumstances (practice, race, passing, familiarity with trail), and health factors (dehydration, sleep, illness). Main outcome measurements: Injuries were reported by proportion (per 100 participants) due to insufficient compliance with exposure reporting. Results: A total of 837 injuries in 554 student-athlete injury events were reported. The most commonly reported injury was concussion (22.2%), followed by injury to the wrist/hand (19.0%), shoulder (15.7%), and knee (13.7%). 48.2% of injury events occurred on downhills. Males and females reported similar injury rates (2.87% and 3.41%, respectively), but females sustained more lower limb injuries (p<0.001). 70.2% of injured athletes were unable to complete the ride. 47.1% of crashes resulted in an emergency room visit. Conclusions: Interscholastic mountain bike racing is a rapidly growing sport. Acute traumatic injuries are common, including concussions and injuries to the upper extremities. Male and female riders have similar injury rates but different injury types. To our knowledge, this is the largest mountain bike racing ISS in existence.